"I don't want to be near you, unless…": The interactive effect of unethical behavior and performance onto relationship conflict and workplace ostracism. Issue 3 (29th April 2016) - Quade, Matthew J.; Greenbaum, Rebecca L.; Petrenko, Oleg V.
Abstract : Examined through the lens of moral psychology, we investigate when and why employees' unethical behaviors may be tolerated versus rejected. Specifically, we examine the interactive effect of employees' unethical behaviors and job performance onto relationship conflict, and whether such conflict eventuates in workplace ostracism. Although employees' unethical behaviors typically go against moral norms, high job performance may provide a motivated reason to ignore moral violations. In this regard, we predict that job performance will mitigate the relationship between employee unethical behavior and workplace ostracism, as mediated by relationship conflict. Study 1, a multisource field study, tests and provides support for Hypotheses 1 and 2. Study 2, also a multisource field study, provides support for our fully specified model. Study 3, a time‐lagged field study, provides support for our theoretical model while controlling for employees' negative affectivity and ethical environment. Theoretical and practical implications are discussed.